Rancang Bangun e-SPM sebagai Peningkatan Kualitas Ketersediaan Informasi pada LPM IAIN Syekh Nurjati Cirebon (INTI TALAFA, 2024)
In an effort to realize the vision, mission, and objectives of IAIN Syekh Nurjati Cirebon, there is a need for a reference in the form of minimum service standards (SPM) that encompass general criteria in the implementation of education. These SPM aim to enhance the performance of educational services and promote public transparency and accountability. In line with the BLU legal mandate, government educational institutions are required to be efficient and effective in providing services, with a focus on the professionalism of human resources. The formulation of SPM at IAIN Syekh Nurjati Cirebon considers principles of simplicity, concreteness, measurability, openness, affordability, and accountability. The SPM covers services related to education, research, community service, administration, digital transformation, halal center, and business development. The development of the SPM application through five stages has resulted in an accessible application managing SPM data at http://lpm.syekhnurjati.ac.id:8000, enabling improved performance in the management of SPM documents at IAIN Syekh Nurjati Cirebon.